Estado actual del conocimiento sobre el fenomeno de la intimidacion escolar a partir de lo publicado en revistas colombianas de psicologia indexadas en publindex, 2005 - 2021: Intimidación escolar en Colombia - Marques Ayala , Yolys Carolina; Castro Henao , Yuvined (Corporación Universitaria Iberoamericana - Repositorio de Trabajos de Grado, 2023)
The purpose of this study is to elaborate a state of current knowledge on school bullying and victimization in Colombia through the documentary review of specialized journals in Psychology indexed in the National System of Indexation and Homologation Publindex (Colciencias). The methodology of this study is the card construction model proposed by Consuelo Hoyos (2000) of the University of Cauca for the elaboration of states of art or current knowledge. In this research, 21 journals were selected that generated 80 articles, which were grouped according to the Colciencias typology for scientific articles and were partially analyzed to later build a global theoretical analysis. It was found that Colombian psychology journals that have published on the subject are likely to be classified either in category A or category C and that the authors who publish have not fully built a network of collaborations. The conclusions of the reviewed investigations tend to coincide with world trends in methods and results. A conceptual discussion of the results found is offered.